Assessing the Sustainability of Advanced Materials Using Multicriteria Decision Analysis and the Triple Bottom Line. (21st October 2019) - Rycroft, Taylor; Wood, Matthew; Zemba, Valerie; Kennedy, Alan; Weiss, Charles; Desmet, David; Ali, Rahim; Linkov, Igor
ABSTRACT: Although advanced materials (AdMs) are beneficial in many applications, questions remain as to whether they are more or less sustainable than the conventional materials that they may replace. Currently, there is no available tool to provide clarity to these questions. Traditional approaches for evaluating the sustainability of a chemical or material are usually not standardized, and as a result, the metrics used in sustainability measurements are subjective and often vary from assessor to assessor. Additionally, sustainability characterizations resulting from these approaches are typically presented qualitatively and are often vaguely drawn, making it difficult to confidently and transparently conclude that 1 material is more sustainable than another. This paper aims to address these gaps by enabling stakeholders involved in the production, use, or governance of AdMs to assess the sustainability of AdMs in a consistent, objective, and quantitative way using a multicriteria decision analysis (MCDA)–based model. The model proposed herein adapts a triple‐bottom‐line (TBL) framework from the Institution of Chemical Engineers (IChemE) and incorporates criteria weights identified through a stakeholder values assessment conducted by surveying AdM practitioners. Results from the stakeholder values assessment show that the perceived importance of the economic component of the TBL varies the most across stakeholders, and that practitioners providing responses from the perspective of a nongovernmental environmental advocacy group or a regulator of AdMs such as the United States Environmental Protection Agency were more likely to score and weigh economic indicators lower and environmental indicators higher compared to when responding from a business owner perspective. The resulting MCDA‐based model allows stakeholders to assess the sustainability of an AdM or AdM‐enabled product and compare it to product alternatives, predict how other stakeholders might score a product by identifying the extent to which components of the TBL are valued by other stakeholders, and identify which subcriteria contribute most to an improvement in a product's sustainability score. Integr Environ Assess Manag 2019;00:1–8. © 2019 SETAC Key Points: The multicriteria decision analysis (MCDA)–based sustainability model presented here can be used by stakeholders involved in the production, use, or governance of advanced materials (AdMs) for assessing the sustainability of an AdM or AdM‐enabled product and comparing it to product alternatives. The MCDA‐based sustainability model presented here can be used to predict how other stakeholders might score a product by identifying the extent to which components of the triple‐bottom‐line (TBL) are valued by other stakeholders. The MCDA‐based sustainability model presented here can be used to identify which subcriteria contribute most to an improvement in a product's sustainability score.